Corporate governance in less developed and emerging economies - Tsamenyi, Mathew; Uddin, Shahzad (Emerald, 2009)
Research on accounting in LDCs argues that a well-developed corporate governance structure, including accounting infrastructure, would promote economic prosperity. Economic development requires a modern, transparent corporate governance infrastructure based on efficient capital markets. Over the past decade corporate governance reform has become an important global policy agenda driven by events such as the 1997 Asian financial crisis, major corporate scandals (such as Enron and WorldCom) and the globalisation of capital markets. In several less developed and emerging economies corporate governance reform is also driven by the adoption of international donor led economic reforms. This in particular has made corporate governance reform an essential element of the development agenda promoted by the World Bank. The papers in the volume have provided wide ranging empirical and theoretical issues that will have policy implications and also generate future academic debates. Overall, the volume advances debate on corporate governance, accountability and transparency in less developed and emerging economies. We believe the audience will find the papers interesting and insightful in terms of theoretical development, practices and policy implications.
Keywords: Corporate governance.; International finance.; International economic relations.; elektronické knihy; electronic books